Analisis dinamis tingkat inflasi di Indonesia dengan pendekatan Error Correction Model - Alvis Rozani; Nurul Huda; Zulfanetti Zulfanetti (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This study aims to analyze the influence of the money supply, public consumption, economic growth and interest rates on inflation in Indonesia, using the dynamic error correction model. Based on the results of research on the ECT it shows that the process of adjustment to imbalances in changes in the inflation rate in Indonesia is relatively slow, the money supply in the short and long term has no significant effect on the inflation rate in Indonesia, public consumption in the short and long term has no significant effect on the inflation rate in Indonesia, economic growth in the short and long term has a significant effect on the inflation rate in Indonesia and interest rates in the short and long term have a significant effect on the inflation rate.